2021
DOI: 10.1093/nar/gkab1227
|View full text |Cite
|
Sign up to set email alerts
|

Efficient target cleavage by Type V Cas12a effectors programmed with split CRISPR RNA

Abstract: CRISPR RNAs (crRNAs) that direct target DNA cleavage by Type V Cas12a nucleases consist of constant repeat-derived 5′-scaffold moiety and variable 3′-spacer moieties. Here, we demonstrate that removal of most of the 20-nucleotide scaffold has only a slight effect on in vitro target DNA cleavage by a Cas12a ortholog from Acidaminococcus sp. (AsCas12a). In fact, residual cleavage was observed even in the presence of a 20-nucleotide crRNA spacer moiety only. crRNAs split into separate scaffold and spacer RNAs cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
5
8
0
Order By: Relevance
“…Furthermore, we showed that the trans-addition of a 20-base scaffold RNA rescued the cleavage activity of these enzymes. Thus, we proposed the concept of split crRNA, which, in a complex with V-A nucleases, was comparable to cleavage activity observed with full-sized crRNA [ 17 ]. Here, we expand our observations and investigate the ability of RbCas12 to be programed with split crRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we showed that the trans-addition of a 20-base scaffold RNA rescued the cleavage activity of these enzymes. Thus, we proposed the concept of split crRNA, which, in a complex with V-A nucleases, was comparable to cleavage activity observed with full-sized crRNA [ 17 ]. Here, we expand our observations and investigate the ability of RbCas12 to be programed with split crRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6 A, in reactions containing both full-sized and split crRNAs, the target DNA was cleaved by ~90% under the conditions of the experiment. We previously showed that increasing the spacer-only crRNA concentration could increase the cleavage efficacy of AsCas12a [ 17 ]. The data presented in Figure 6 B demonstrate that increasing the concentration of spacer RNA from 0.5 to 5 μM causes dose-dependent DNA substrate cleavage by RbCas12a.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Shebanova et al (2022) demonstrated that removal of most of the hairpin scaffold did not significantly affect target DNA cleavage by AsCas12a, FnCas12a, and LbCas12a in-vitro and in lysates from human cells. The study showed efficient cleavage caused by AsCas12a charged with high dose of spacer RNA was capable of cleavage of DNA substrates 18 . Contrary, Nguyen et al ( preprint ) observed limited cleavage efficiency of AsCas12a with truncated crRNA.…”
Section: Discussionmentioning
confidence: 97%
“…Engineering of crRNAs is indubitably an attractive approach to design novel functions due to the low cost of polynucleotide synthesis and advances in the understanding of polynucleotide function. crRNAs have been modified to improve editing in a number of ways, namely, by adjusting the length of the 3’ or 5’ regions 16 , 17 , removing majority of the hairpin scaffold 18 , introducing chemical or structural modifications 19 – 22 , or inserting tRNA-like structures or small hairpins in the 3’-end to increase stability 23 . Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of sensitivity is related to the mechanism of Cas12. A recent study reported a startling discovery that AsCas12a programmed with split crRNAs catalyzed cis-cleavage and trans-cleavage [ 58 ]. This mind-boggling finding suggests that many unknown properties of Cas12 remain to be studied.…”
Section: Discussionmentioning
confidence: 99%